Conversion of furfuryl alcohol to ethyl levulinate in the presence of mesoporous aluminosilicate catalyst - Bai Yuli; Liu Yi; Bai Fudong; Sun Qimei; Li Lanpeng; Zhang Tong (Open Chemistry, 2021)
The one-pot acid-catalyzed the conversion of furfuryl alcohol (FA) to ethyl levulinate (EL) was investigated in the presence of mesoporous aluminosilicate (TUD-1) with a high surface area (up to 579 m2 g−1) and well-interconnected mesospheres synthesized via a solvothermal process and characterized using scanning electron microscope, transmission electron microscope, X-ray diffraction, 27Al-NMR, and N2 sorption isotherm. The resulting solid acid catalyst was tested for the alcoholysis of FA with ethanol, affording 87.8% EL yield under the optimal reaction conditions of 120°C and 4 h. Moreover, the catalyst showed a good reusability with less loss of activity after a simple solvent washing and calcination procedure.